The GTPase-Activating Protein FgGyp1 Is Important for Vegetative Growth, Conidiation, and Virulence and Negatively Regulates DON Biosynthesis in Fusarium graminearum - Zheng, Qiaojia; Yu, Zhi; Yuan, Yanping; Sun, Danli; Abubakar, Yakubu Saddeeq; Zhou, Jie; Wang, Zonghua; Zheng, Huawei (Frontiers in Microbiology, 2021)
Gyp1 functions at the Golgi as a negative regulator of Ypt1 in yeast. Gyp1 homologs are conserved in filamentous fungi. However, the roles of Gyp1 in phytopathogenic fungi remain poorly understood. In the present study, we characterized the function of FgGyp1 in the wheat pathogen Fusarium graminearum by live-cell imaging, genetic and pathological analyses. Targeted gene replacement method was used to delete FgGYP1 in F. graminearum. Phenotypic analyses showed that FgGyp1 is critically important for vegetative growth and conidiation of F. graminearum. The vegetative growth of the FgGYP1 deletion mutant reduced by 70% compared to the wild type PH-1. We further found that FgGyp1 negatively regulates DON production of the fungus. Live-cell imaging clearly demonstrated that FgGyp1 mainly localizes to the Golgi apparatus. Moreover, the TBC domain, N-terminal and C-terminal regions of FgGyp1 are found to be indispensable for its biological functions and normal localization. The Arg357 residue of FgGyp1 is essential for its functions but dispensable for the normal localization of the protein, while the Arg284 residue is not required for both the functions and normal localization of the protein. Furthermore, we showed that FgGyp1 essentially hydrolyzes the GTP-bound FgRab1 (activated form) to its corresponding GDP-bound (inactive) form in vitro, suggesting that FgGyp1 is a GTPase-activating protein (GAP) for FgRab1. Finally, FgGyp1 was found to be important for FgSnc1-mediated fusion of Golgi compartment-derived secretory vesicles with the plasma membrane in F. graminearum. Taken together, these results indicate that FgGyp1 acts as a GAP for FgRab1 and is critical for vegetative growth, conidiation and pathogenicity, and negatively regulates DON biosynthesis in F. graminearum.